Canadian Public Health Laboratory Network Laboratory Guidelines for the Use of Direct Tests to Detect Syphilis in Canada. (2015) - Tsang, Raymond SW; Morshed, Muhammad; Chernesky, Max A; Jayaraman, Gayatri C; Kadkhoda, Kamran
Abstract : Treponema pallidum subsp. pallidum and/or its nucleic acid can be detected by various methods such as microscopy, rabbit infectivity test or polymerase chain reaction (PCR) tests. The rabbit infectivity test for T. pallidum, although very sensitive, has been discontinued from most laboratories due to ethical issues related to the need for animal inoculation with live T. pallidum, the technically demanding procedure and long turnaround time for results, thus making it impractical for routine diagnostic use. Dark-field and phase-contrast microscopy are still useful at clinic- or hospital-based laboratories for near-bedside detection of T. pallidum in genital, skin or mucous lesions although their availability is decreasing. The lack of reliable and specific anti- T. pallidum antibodies and its inferior sensitivity to PCR may explain why the direct fluorescent antibody test for T. pallidum is not widely available for clinical use. Immunohistochemical staining for T. pallidum also depends on the availability of specific antibodies, and the method is only applicable for histopathological examination of biopsy and autopsy specimens necessitating an invasive specimen collection approach. With recent advances in molecular diagnostics, PCR is considered to be the most reliable, versatile and practical for laboratories to implement. In addition to being an objective and sensitive test for direct detection of Treponema pallidum subsp . pallidum DNA in skin and mucous membrane lesions, the resulting PCR amplicons from selected gene targets can be further characterized for antimicrobial (macrolide) susceptibility testing, strain typing and identification of T. pallidum subspecies.